Fuzzy Multicriteria Model for Ranking Suppliers in Manufacturing Company - Željko Stević; Ilija Tanackov; Marko Vasiljević; Slavko Vesković (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
By using the methods of multi-criteria analysis it is possible to make decisions which have significant influence on companies' business. The aim of this paper is to evaluate different suppliers using the integrated model that recognizes a combination of fuzzy AHP (Analytical Hierarchy Process) and the COPRAS method. Based on six criteria, the expert team was formed to compare them, so determination of their significance is being done with fuzzy AHP method. Expert team also compares suppliers according to each criterion and on the base of triangular fuzzy numbers. Based on their inputs, COPRAS method is used to estimate potential solutions. Suggested model accomplishes certain advantages in comparison with previously used traditional models which were used to make decisions about evaluation and choice of supplier. It is vital to make the right decision when selecting a supplier, because the optimal choice ensures lower cost and higher quality of the product itself, and therefore more competitiveness in the market.
Keywords: C44; C52; C61; D22; D81; M11; L6; 330; Multi-criteria decision making; supplier evaluation; Fuzzy AHP; COPRAS; procurement; research; decision support systems